How fire and climate shaped grass-dominated vegetation and forest mosaics in northern South Africa during past millennia - Breman, E; Gillson, L; Willis, K (SAGE Publications, 2011)
Grassland and savanna are globally important ecosystems, both ecologically and economically. These grass-dominated systems are at risk from current and future climate change and increasing anthropogenic impact. Key questions for understanding the resilience and variability of grass-dominated ecosystems under current and future environmental conditions include: How have these systems responded to climate change and disturbance in the past? What are the principal driving agents responsible for their present-day composition and distribution? Do the palaeoecological data provide evidence for feedbacks between climate, fire and anthropogenic activities? In this study, the temporal dynamics of grassland, savanna and forest in the summer rainfall region of northern South Africa were reconstructed for the last ~6500 years. Palaeoecological techniques used include analyses of fossil pollen, charcoal and stable isotopes. Data from two sites located at the present-day grassland-savanna ecotone in Mpumalanga province of South Africa are reported. Results indicate that a mosaic of grassland, savanna and Podocarpus forest occupied the landscape throughout the late Holocene, with grassland and forest dominating higher altitudes, and savanna and forest lower altitudes. Podocarpus forest retreated and grass-dominated vegetation expanded its range around 1800 cal. yr BP at the lower altitude site (Lowveld) and 600 cal. yr BP at the higher altitude site (Highveld), representing a change from a stable state forest savanna/grassland mosaic to an increasingly grass-dominated system. Climatic stress, changes in fire regime and anthropogenic impact led to the vegetation transitions recorded, and resulted in changes in water and nutrient cycles. In an increasingly warm world, with fluctuating water availability and heightened anthropogenic use of natural resources, the future of grass-dominated ecosystems appears far from stable.